Refocusing on nature: the role of nature reintegration in environmental, mental, and societal wellbeing - Willis, Royce L.; Brymer, Eric; Sharma-Brymer, Vinathe; Leach, Matthew (Frontiers in Psychology, 2024)
This perspective paper investigates the dynamic interplay between wealth, materialism, environmental degradation, and mental health amid escalating challenges of climate change. The paper critically examines how affluence, often a buffer against climate impacts, paradoxically leads to higher consumption and carbon footprints, exacerbating environmental problems. A societal emphasis on materialism contributes to an estrangement from nature, with significant implications for mental health and environmental sustainability. The paper proposes a fundamental shift in addressing these intertwined challenges through reintegration with nature. The paper recommends integrating urban planning, education, mental health, and community engagement strategies to build a sustainable, mentally resilient society more integrated with nature. This approach, supported by future research directions, aims to create a more balanced, environmentally conscious, and mentally healthy world.